PENDAMPINGAN EVALUASI KAPASITAS STRUKTUR BANGUNAN GEDUNG EKSISTING TERHADAP BEBAN GEMPA BERDASARKAN SNI 1726:2019 DAN KONDISI KELAS SITUS TANAH GAMBUT - Erdin Fahlefi; Ashraf Dhowian Parabi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Existing buildings in Pontianak City designed prior to SNI 1726:2019 are potentially deficient in structural seismic capacity due to the absence of site amplification corrections for peat soil Site Class SE, which carries significant Fa and Fv factors. This community service program (PKM) aimed to mentor seven structural consultants at CV. Bhipraya Cipta, Pontianak, in mastering the seismic capacity evaluation procedure for existing buildings under SNI 1726:2019, encompassing site-specific design response spectrum construction, modal response spectrum analysis, and demand-capacity ratio (DCR) verification of structural elements. The activity was conducted over one full day using a three-phase method: needs assessment through pre-test, two-session technical mentoring assisted by ETABS software, and evaluation through post-test. The evaluation instrument comprised 25 items covering five competency indicators specific to existing structural capacity evaluation. Results showed an improvement in average scores from 38.7 to 81.3 with an overall normalized gain (g-score) of 0.69 (medium category), along with identification of three major procedural gaps in existing capacity evaluation practice, forming the basis for structured technical mentoring recommendations.